2017
DOI: 10.5152/iao.2016.2300
|View full text |Cite
|
Sign up to set email alerts
|

Speech-Evoked Auditory Brainstem Response in Individuals with Diabetes Mellitus Type 2

Abstract: RESULTS:The findings of the current study suggest that middle-aged individuals with diabetes have a significant deficiency in auditory processing at the brainstem level. Both transient (wave V (p=0.00), A (p=0.00), and O (p=0.00)) and sustained responses (wave D (p=0.001), E (p=0.00), and F (p=0.00)) of the S-ABR were found to be affected in diabetic individuals compared to age-matched non-diabetic individuals. CONCLUSION:Considering diabetes is a common metabolic disorder in the middle-aged Indian population,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…16 With respect to how speech signals are processed at the subcortical level in DM2, Gupta et al 43 found that the latency and amplitude for both transient and sustained responses were significantly reduced in DM2 individuals compared with individuals without DM2. A similar trend with respect to latency was reported by Sanju et al 44 for the transient and sustained responses of the speech-evoked response Thus, these findings are ascribed to factors such as reduced outer hair cell activity, impaired neuronal conduction time, and degeneration at the level of the brainstem.…”
Section: Audiological Evaluation In Type-2 Diabetes Mellitussupporting
confidence: 85%
“…16 With respect to how speech signals are processed at the subcortical level in DM2, Gupta et al 43 found that the latency and amplitude for both transient and sustained responses were significantly reduced in DM2 individuals compared with individuals without DM2. A similar trend with respect to latency was reported by Sanju et al 44 for the transient and sustained responses of the speech-evoked response Thus, these findings are ascribed to factors such as reduced outer hair cell activity, impaired neuronal conduction time, and degeneration at the level of the brainstem.…”
Section: Audiological Evaluation In Type-2 Diabetes Mellitussupporting
confidence: 85%
“…The need to develop research methods that are objective and accurately represent daily listening led to the development early this century of electrophysiological tests for measuring how speech sounds are perceived [1,2]. Subsequently, a number of research groups have focused their efforts on using complex stimuli such as speech for diagnostic purposes [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%